2020
DOI: 10.1089/mdr.2020.0269
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, Resistance, and Genomic Fingerprint Traits ofVibrio choleraeIsolated from 12 Species of Aquatic Products in Shanghai, China

Abstract: Vibrio cholerae is a waterborne bacterium and can cause epidemic cholera disease worldwide. Continuous monitoring of V. cholerae contamination in aquatic products is imperative for assuring food safety. In this study, we determined virulence, antimicrobial susceptibility, heavy metal tolerance, and genomic fingerprints of 370 V. cholerae isolates recovered from 12 species of commonly consumed aquatic products collected from July to September of 2018 in Shanghai, China. Among the species, Leiocassis longirostri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 63 publications
5
32
2
Order By: Relevance
“…The hapA gene encodes a hemagglutinin protease secreted by V. cholera through the type II secretion system that functions in V. cholerae interactions with aquatic hosts [ 7 , 33 ]. Studies have reported that most V. cholerae strains carry the hap gene irrespective of their source (i.e., clinical or environmental) [ 6 , 9 , 34 ], consistent with our present results. RTX is essential for the cytotoxic activity of V. cholerae O1 El Tor strain upon Hep-2 cells in vitro [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The hapA gene encodes a hemagglutinin protease secreted by V. cholera through the type II secretion system that functions in V. cholerae interactions with aquatic hosts [ 7 , 33 ]. Studies have reported that most V. cholerae strains carry the hap gene irrespective of their source (i.e., clinical or environmental) [ 6 , 9 , 34 ], consistent with our present results. RTX is essential for the cytotoxic activity of V. cholerae O1 El Tor strain upon Hep-2 cells in vitro [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Serratore et al reported that 28 batches of edible snails ( Nassarius mutabilis and Bolinus brandaris ) in the Adriatic Sea were negative for E. coli , Vibro vulnificus , and V. cholerae contamination [ 22 ]. In this study, our results also provided additional evidence to demonstrate high detection frequencies of V. cholerae in fish species such as A. nobilis , C. auratus , and P. pekinensis , consistent with results of our prior research [ 6 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations